KETERAMPILAN BERKOMUNIKASI SISWA MELALUI PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE EVERYONE IS A TEACHER HERE (ETH) PADA MATERI KALOR DI KELAS VIIA SMP BEER SEBA PEKANBARU - Riska Yani Butar-Butar; M.Nor '; Azizahwati ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study attempts to described conversation skills students after implementing learning active type Everyone is a Teacher Here (ETH). The kind of research used is quasi experiment, to a draft one-shot case study. The subject of study this is a student VIIA amounted to 28 students. Design this research are those in small quantities given treatment / the treatment is as the independent variable, and the result is as variable dependent ), and then observed the results. An instrument data collection in this research was sheets of direct observation. Data analysis in this research was descriptive analysis quantitative to see category conversation skills students. From the data analysis, shows that percent conversation skills oral students an average of 47,25% that characterizes medium category. While for conversation skills written students an average of 85,35% were classified in the category very high. Where every encounter is increasing every indicator. Thus,can be concluded that the implementation of learning active type Everyone is a Teacher Here can be used as alternatives in the teaching process in class VIIA Junior High School Beer Sheba Pekanbaru.